HBR guide to smarter networking - Harvard Business Review. (Harvard business review guides., 2022)
"We know that the key to getting ahead and launching our ideas is building and sustaining a high-quality and diverse network. But the days of handing out hundreds of business cards at conferences and hoping for the best are over. Our networks need to be both strategic and authentic, made up of real relationships that bring real value. The HBR Guide to Smarter Networking will give you the tools and the confidence you need to make valuable connections, get your ideas off the ground, draw on others' expertise, scope out business opportunities, and land coveted roles. This guide will help you: Connect with connectors; nourish relationships through give and take; get the most out of conferences-in-person or virtual; use your limited networking time wisely; maintain loose ties over long periods; and emphasize quality of contacts over quantity"--